Distinguishing high engagement from problematic symptoms in Instagram users: Associations with big five personality, psychological distress, and motives in an Italian sample - Davide Marengo; Alessandro Mignogna; Jon D. Elhai; Michele Settanni (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace)
Building on recent findings by Fournier and colleagues (2023), the present study examined the fit of a bi-dimensional model of problematic Instagram use, distinguishing between non-pathological high engagement and problematic symptoms mirroring addictive tendencies. A sample of 696 Italian adults completed an online survey assessing problematic Instagram use, personality traits, psychological distress, usage motives for Instagram use, and Instagram usage metrics. Confirmatory factor analysis supported the bi-dimensional model, with high engagement (salience and tolerance) and problematic symptoms (relapse, withdrawal, conflict, and mood modification) as distinct factors. Neuroticism, depression, emotional dysregulation, loneliness, and FoMO and the diversion motive were more strongly correlated with problematic symptoms. In turn, social interaction, documentation, and self-promotion were more associated with high engagement. Frequency of sharing posts and stories were also more strongly correlated with high engagement. These findings highlight the importance of distinguishing between high engagement and addiction-like symptoms in understanding problematic Instagram use and inform the development of targeted interventions.